Chronic toxoplasmosis and possible risk factors associated with pregnant women in Khyber Pakhtunkhwa. Issue 4 (3rd July 2016) - Majid, Abdul; Khan, Sanaullah; Jan, Abdul Hamid; Taib, Muhammad; Adnan, Muhammad; Ali, Ijaz; Khan, Shahid Niaz
ABSTRACT: Toxoplasmosis is the major cause of abortion and stillbirths among women of childbearing age. The aim of this study is to determine chronic Toxoplasma gondii infection at various trimesters of pregnancy and to identify various possible routes of transmission and contamination in North-West Pakistan. A total of 733 blood samples were randomly obtained from antenatal/maternity centres. A detail questionnaire was designed to analyse the clinical history of the subjects tested for specific anti-Toxoplasma IgG antibodies by using immunofluorescence assay. Overall toxoplasmosis was detected in 18.41% of the studied population. Anti-Toxoplasma IgG was found 7.17% in first trimester with highest prevalence 31.28% in third trimester. Increase in the prevalence of parasite was seen with rise in age highest found in higher age group ( P ˂ 0.05). As compared to district Lower Dir and Swat, Upper Dir had high rate 33.03% of chronic infection. Consumption of undercooked meat was also found 45.22% related with the prevalence of infection. A significant relation was observed with level of education ( P ˂ 0.05) and prevalence of toxoplasmosis. An association was observed between prevalence of T . gondii infection and various risk factors, i.e. consumption of raw eggs, vegetables, contact with cats, cattle, soil, water sources and use of unpasteurized milk. This study shows high prevalence of the parasite in the studied area. Pregnant women in contact with cats were found more at risk. Education of childbearing age women, personal hygiene and contact with soil was also found important possible risk factors in the spread of infection.